Implementasi Living Curriculum terhadap Kondisi dan Lingkungan Siswa di Sekolah Indonesia Kuala Lumpur Guna Terciptanya Generasi Unggul, Cerdas dan Berkepribadian Bangsa - Rakanita Dyah Ayu Kinesti; Nico Khoirun Ni'am; Siti Shaidah; Siti Musyafaroh; Elma Nur Santika; Mustamaroh Mustamaroh (FONDATIA, 2021)
Overseas Indonesian schools in Kuala Lumpur were established to meet the educational needs of children of diplomats or local staff at the Indonesian representative office. In addition, it is also for children of Indonesian citizens who work in related countries and live in that country. Along with the high dynamics of community interaction between friendly countries, the Kuala Lumpur International School of Indonesia also functions as a balanced and comprehensive service for education and development of Indonesian culture in the local country. This research aims to determine how the Living Curiculum applies to the conditions of students and the environment at Kuala Lumpur Foreign Schools. This research was conducted qualitatively, namely using the perspective of the participants as an illustration in getting the results of the research. The results of the research at SIKL (Sekolah Indonesia Kuala Lumpur) apply a national curriculum but are tailored to the needs of students, especially those who live in Kuala Lumpur, why is that, because the conditions of students in Kuala Lumpur are different from those of students in Indonesia. The implementation of the Living curiculum or life curriculum at SIKL has two learning models, namely Learning at School (LAS) and Learning at Home (LAH). The Living curiculum application is carried out to create a new generation that is superior, intelligent and has a high national personality.